Inovasi Mesin Pencetak Lidah Rokok Guna Meningkatkan Output Produksi di CV. Langgeng Jaya - Fawwaz Ruly Saputra; Hery Murnawan (Fakultas Teknik UMRI, 2024)
Cigarette packs are rectangular packages made mostly of cardboard containing cigarettes. Packaging is designed from aluminum foil, paper or flavor-protecting plastic and sealed with clear, airtight plastic film. Production process at CV. Langgeng Jaya has 2 types and they are still very inefficient. So, looking at this problem, a proposal is given to innovate a cigarette tongue printing machine to make the cigarette tongue printing machine more efficient and speed up the production process. Innovation: The cigarette tongue molding machine is designed using dimensions from anthropometric calculations and the 50th percentile of workers, so that the height of the material support is 103.75 cm, determines the material entry route of 69.5 cm, and determines the height of the panel box of 93.5 cm. Machine trials must be carried out to determine the difference in output after designing the machine innovation and before the design is carried out. The resulting output must be compared before the innovative design of the cigarette tongue machine is carried out and after the design is carried out. The output produced before the design was carried out was 192, after the innovative design of the cigarette tongue printing machine was carried out, it was 320 kg a day. The increase in productivity after designing the innovative cigarette tongue printing machine was 66%, which means it was successful.